Postoperative Bleeding in CABG Patients: New Study in Southwest of Iran - Heidari, Amanollah; Firoozabadi, Mehdi Dehghani; Sheikhi, Mohammad Ali (BALI MEDICAL JOURNAL, 2016)
Background: A common complication after Coronary Artery Bypass Grafting (CABG) is postoperative bleeding, which is considered as an important problem. Objective: The aim of this study is to study only patients who have never used drugs above so that it can assess postoperative bleeding in CABG with the absence of high-risk medications related to postoperative bleeding. Method: 50 patients who were candidates for CABG surgery participated in the study. Inclusions criteria included who were candidates for CABG surgery, avoiding the use of blood-clotting drugs before surgery, avoiding the use of immunosuppressant, and the absence of an underlying medical condition such as kidney diseases. Patients with inflammatory, platelet diseases, or any coagulation disorder were excluded. All patients initially tested for hemoglobin, platelets and hemoglobin and INR. In addition to testing for hemoglobin, the amount of bleeding and packed red cell; frozen plasma and platelets were recorded. Results: Fifty patients who were candidates for elective surgery, including 33 men (66%) and 17 women (34%) were enrolled in this study. The mean patient age was 8.70+57.9years old. Test showed that mean hemoglobin level of patients before surgery was pre- operative of 1.5 + 12.4 g/dL, mean platelet was equal to 54.14 + 250.8 thousand/µL and an average international normalized ratio (INR) was equal to 0.12+1.07. The results after surgery also showed that: The total units of given packed red cell; frozen plasma and platelets were (3.14 + 1.90; 2.34 + 2.36 and 0.06 + 0.42). Also, postoperative hemoglobin was 1.30 + 10.30 g/dL, which significantly decreased compared to pre-operative hemoglobin. Bleeding in patients was observed with an average of 537.5 + 973 mL. Of course, the amount of bleeding in any patient was not caused further surgery, Conclusion: that the use of some drugs surgery can be a good way to reduce the risk of bleeding after surgery or on-use of some drugs can reduce the risk of bleeding after surgery with a minimum of morbidity and mortality. It is suggested that other researchers after designing clinical trials and using lower doses for effective drugs such as Clopidogrel and compared to control groups, or different doses of the N-acetylcysteine drug be reported more documentation to improve the bleeding after surgery.